The liability of foreignness in international equity investments : evidence from the US stock market - Baik, Bok (2013)
Using foreign institutional ownership data in the US from 1990 to 2007, we examine whether foreign institutional investors face liabilities of foreignness (LOF) in the US stock market. We find that foreign institutional investors prefer low information asymmetry stocks more than domestic institutional investors do, and this preference for low information asymmetry stocks is particularly strong among foreign institutional investors from countries with high LOF. More importantly, we find that a change in foreign institutional ownership is negatively related to future returns, whereas this relation does not exist for domestic institutional ownership. The negative relation between the change in foreign institutional ownership and future returns is more pronounced when investors face a greater LOF in the US stock market – for instance, when they are from countries with higher institutional distance, information asymmetry, unfamiliarity, and cultural differences. The negative effect of country-specific LOF factors on the return-forecasting power of foreign institutional investors is more evident when they trade stocks with higher information asymmetry. Overall, these findings suggest that foreign institutional investors face significant LOF costs in the US stock market, resulting in their poor ability to forecast returns.